The association between antenatal SARS-CoV-2 exposure and infant neurodevelopment at four months of age: A prospective multicenter cohort survey within the COPE study - Johan Berg; Karolina Linden; Mehreen Zaigham; Magnus Domellöf; Fredrik Ahlsson; Anders Elfvin; Ulrika Åden; Thomas Abrahamsson; Andreas Ohlin; Johannna Berg; Linda Hjertberg; Sofie Graner; et al. (International Journal of Infectious Diseases, 2025)
Objectives: It remains unclear whether antenatal SARS-CoV-2 exposure affects subsequent infant neurodevelopment. We aimed to investigate the association between antenatal maternal SARS-CoV-2 infection and neurodevelopment in four-month-old infants. Methods: Data was collected within the prospective multicenter COVID-19 during pregnancy and early childhood study, COPE (NCT04433364). Infants exposed to maternal SARS-CoV-2 infection from conception until two days postpartum and unexposed controls were included June 2020-December 2022. Primary outcome: four-month-old infant neurodevelopment, measured using the Ages and Stages Questionnaire 3rd Edition (ASQ) total mean scores. Secondary outcomes: Scores below cutoff for total ASQ or the ASQ domains. Results: Of 2453 enrolled infants, 1446 (555 exposed and 891 unexposed) had available ASQ data. In adjusted regression models, there was no group difference in ASQ total mean scores. Exposed infants had lower risk of fine motor domain scores below cutoff (exposed: 4.0% vs. unexposed: 6.6%; adjusted odds ratio (aOR), 0.55; 95% CI, 0.33-0.92). Infants exposed to severe maternal COVID-19 had increased risk of total ASQ scores below cutoff (exposed: 16.0% vs. unexposed: 6.1%; aOR, 3.57; 95% CI, 1.14-11.24). Conclusions: Antenatal maternal SARS-CoV-2 infection was not associated with overall impaired four-month infant neurodevelopmental screening. In exploratory analyses, severe maternal COVID-19 was associated with abnormal screening results.